(untitled) (The Peerian Journal, 2024)
One of the most common bacterial groups in the oral bacterial ecology is the Viridans Group Streptococci (VGS). In Iraq, DC is widely used, affecting people of all ages. The purpose of this research was to identify the role of VGS bacteria in DC, their capacity to produce specific virulence factors, and their antimicrobial resistance to commercially available antibiotics . This crosssectional study was carried out between August 2020 and June 2021 in Al-Nasiriyah City, in the province of Thi Qar, Iraq. Patients with DC provided 250 dental caries swabs in total. Patients were allocated from the Specialized Center of Dentistry and Sumar Specialized Dentistry Center in AlNasiriyah city. The age range was 7-59 years(male and female). Version 27 of the Statistical Package of Social Science (SPSS) was used for the statistical analysis. If the P value is less than 0.05, the difference was deemed significant. After swabbing all of the samples onto blood and MacConkey agar plates, they were all microaerobically cultured for a full day. Vitek 2 system, biochemical testing, and morphological analysis were used to isolate and identify SVG bacteria. Using the disk diffusion method on Muller-Hinton agar plates in accordance with the Kirby-Bauer method, antibiotic susceptibility was assessed for each isolate against 13 antibiotics before the MIC test. 16 sRNA gene positivity was observed in 84.3% of the isolates, while the antibiotic gene detection rate was as follow, ermB (72.0%), PBP1a (82.0%), PBP2b (90.0%), Van A (47.6%), Van C (76.0%) and tetM (80,0%). In conclusion, the present study found that high rate of VGS were recovered from dental caries from different age groups. The isolates showed high resistant rates to a wide range of commercially available antibiotics.